In defense of partisanship - Zelizer, Julian E. (New York, NY : Columbia Global Reports, 2025)
"This book reimagines what partisanship might look like going forward from today. A new era of party-oriented reforms has the potential to pay respect the deep differences that divide us while simultaneously creating a more functional path on which two responsible political parties compete to shape policy while still being able to govern"--
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on January 21, 2025).
JSTOR
Keywords: Two-party systems -- United States; Opposition (Political science) -- United States; Party affiliation -- United States; Bipartisme -- États-Unis.; Opposition (Science politique) -- États-Unis.; Partis politiques -- Adhésion -- États-Unis.; POLITICAL SCIENCE / Political Process / Political Parties; Electronic books